The Position of Childless Widows as Heirs to Husband's Inheritance (Comparative Analysis of Islamic Law Compilation and Civil Inheritance Law) - Sittihajar Muhammad; Baharuddin HI; Suwarti Suwarti (Syntax Corporation Indonesia, 2023)
-